2005
DOI: 10.1080/07373930500340494
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Drying of Wood Strands

Abstract: Characteristics of microwave drying of wood strands with different initial moisture contents and geometries were investigated using a commercial 10 small microwave oven under different power inputs. Temperature and moisture changes along with the drying efficiency were examined at different drying scenar ios. Extractives were analyzed using gas chromatography=mass spectrometry (GC=MS). The results showed that the microwave drying process consisted of three distinct periods (warm-up period, evaporation period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 9 publications
3
18
0
5
Order By: Relevance
“…However, this method leads to serious injury such as the worsening of the taste, color, and nutritional content of the dry product; decline in density and water absorbance capacity; as well as shift of the solutes from the internal part of the drying material to the surface, due to the long drying period and high temperature. [5,6] Other adverse effects include water rehydration capacity and movement of the drying material. The most common method used in the drying of foodstuffs is convective drying.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method leads to serious injury such as the worsening of the taste, color, and nutritional content of the dry product; decline in density and water absorbance capacity; as well as shift of the solutes from the internal part of the drying material to the surface, due to the long drying period and high temperature. [5,6] Other adverse effects include water rehydration capacity and movement of the drying material. The most common method used in the drying of foodstuffs is convective drying.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies covered fruits (Mousa and Farid 2002;Meda et al 2008;Sunjka et al 2004;Dadali et al 2007;Wang et al 2009), grains and oilseeds (Lupinska et al 2009;Walde et al 2002), leafy plant parts (Cui et al 2004;Ozkan et al 2007), and bulbs, tubers, and root crops (Song et al 2009;Lin et al, 1998;Sharma and Prasad, 2001). Areas commonly investigated include drying kinetics (Song et al 2009;Drouzas et al 1999), energy consumption and drying efficiency (Mousa and Farid 2002;Meda et al 2008;Wang et al, 2009;Du et al, 2005), and retention of selected product quality characteristics (Cui et al 2004;Sunjka et al 2004;Lin et al 1998;Alibas 2006;Ozkan et al 2007;Lupinska et al 2009). While these studies showed that the use of microwave energy could be an attractive method for drying plant materials, there is limited literature on the economic implications of its incorporation in the commercial processing of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…A number of industrial systems for microwave vacuum drying are described in [1][2][3][4][5]. Such systems are supposed mainly for stationary processing of considerably large contents of wooden products.…”
Section: Introductionmentioning
confidence: 99%